EFEKTIVITAS MEDIASI DALAM PENYELESAIAN SENGKETA PROSES PEMILU TAHUN 2024 YANG BERKEADILAN - Tobing, Rudyanti Dorotea; Nugraha, Satriya; Putra, Rengga Kusuma (Universitas Stikubank, 2024)
Article 468 paragraph (3) of the Election Law mandates that Bawaslu and its regional offices carry out the Settlement of Election Process Disputes (PSPP) through mediation or deliberation and consensus. This mediation is not optional but obligatory, aiming to reach an amicable agreement between the disputing parties. This process reflects Indonesia's local wisdom in resolving disputes peacefully through deliberation. Mediation or deliberation embodies Indonesia’s local wisdom in peacefully resolving disputes, providing psychological and political peace of mind for the parties involved through a win-win solution approach. In PSPP, mediation is prioritized to achieve a fair agreement for all disputing parties. The method used is normative juridical and employs descriptive analysis. In the 2024 elections, the number of PSPP applications decreased significantly, but the quality of dispute resolution through mediation improved. According to Bawaslu RI data as of March 25, 2024, 64.46% of disputes at the stage of determining the Provisional Candidate List (DCS) and the Final Candidate List (DCT) were resolved through mediation, 83.87% at the stage of changes to the DCT, and 97.34% for the Settlement of Disputes between Election Participants (PSAP). For the verification and determination of political parties, 16.67% were resolved through mediation. This success was supported by mediator training, the enhancement of election supervisors’ capacities, as well as representative technical guidelines from Bawaslu RI, along with the strong commitment of all election supervisors.